A higher burden of post-stroke depression and anxiety and their predictors among stroke survivors in the Amhara Regional State, Ethiopia, in 2024: a prospective multicenter study - Biruk Lelisa Eticha; Ermias Solomon Yalew; Destaw Marie Merawie; Samuel Teferi Chanie; Kaleb Assegid Demissie; Biruktawit Lelisa Eticha (Frontiers in Psychiatry)
BackgroundA substantial proportion of stroke survivors suffer from post-stroke depression and anxiety. These mental disorders are linked to several modifiable risk factors and lead to severe functional impairment or premature death. There is a lack of evaluation, prevention, and treatment of these prevalent mental illnesses. This study aimed to investigate the overall burden of post-stroke depression and anxiety and their predictors in the Amhara Regional State, Ethiopia, in 2024.MethodsFrom 01 February to 01 April 2024, a multicenter cross-sectional study was conducted on 404 stroke survivors from five comprehensive specialized hospitals in the Amhara Regional State, Ethiopia. Five trained physiotherapists conducted interviews, reviewed medical records, and took physical measurements using a pretested, semi-structured questionnaire to obtain high-quality data for analysis. Descriptive statistics were taken into consideration to provide a broad overview of the data and distribution of conditions. Additionally, binary logistic regression was used to find predictors with a p-value of less than 0.2 that could be subjected to multivariate logistic regression analysis, which was used to find the significant associated factors. A p-value of less than 0.05 with a 95% confidence interval (CI) was deemed significant.ResultsThe prevalence of post-stroke depression and anxiety among stroke survivors in the Amhara Regional State was 64.1% (95% CI: 59.3–68.6%) and 45.5% (95% CI: 40.7–50.4), respectively. Variables including male sex [adjusted odds ratio (AOR)=1.97, 95% CI: 1.06–3.67], stroke complication presence (AOR=2.83, 95% CI: 1.64-4.88), and comorbidity presence (AOR=6.23, 95% CI: 3.91–9.19) were significantly associated with post-stroke depression. Retirement (AOR=1.64, 95% CI: 1.91–4.72), less time for hospitalization (AOR=2.05, 95% CI: 1.09–3.84), and comorbidity presence (AOR=2.09, 95% CI: 1.32–3.29) were the significantly associated factors of post-stroke anxiety.ConclusionsRelatively higher burdens of post-stroke depression and anxiety were observed among stroke survivors in the Amhara Regional State, Ethiopia. Variables such as sex, stroke complication, and comorbidity, and retirement, time for hospitalization, and comorbidity were predictors significantly associated with post-stroke depression and anxiety, respectively. Early mental health screening and diagnosis of old age, complicated case patients, and retired stroke survivors are required for early-stage interventions.